PENGARUH MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR KELURAHAN TANJUNG SELOR HILIR KECAMATAN TANJUNG SELOR KABUPATEN BULUNGAN - Wempi Feber,; Iskandar, Iskandar (Juremi: Jurnal Riset Ekonomi, 2024)
This research aim to know how big influence of motivation work and discipline work to officer performance by together and by parsial. Research type taken is quantitative with approach of survey. As for method data collecting of research use observation technique, kuesioner, documentation, and book study. While research data analyzer use doubled linear regression analysis constructively program of SPSS version 20.0. In this research of sampel the used to amount to 11 people. While research variable consist of 2 (two) independent variable and 1 (one) of dependent variable. Pursuant to result analysis research data constructively program of SPSS version 20.0 know that indicator or instrument used to measure motivation variable (X1) proven valid and reliable. That way also for the variable of discipline (X2) and officer performance variable (Y). Result analysis doubled linear regression of for the variable of research indicate that by together motivation variable simultan (X1) and discipline variable (X2) have influence which isn’t it to officer performance variable (Y) where F value bigger than F value is tables of with value that is 7,070 > 4,459. Later than result of test of t research variable by parsial that motivation variable (X1) have influence which isn’t it to officer performance variable (Y) with acquirement of value of t bigger than value of t the tables of that is 3,315 > 2,306. While discipline variable (X2) don’t have influence which isn’t it to officer performance variable (Y) because value of t bigger than value of the tables of that is 1,209 < 2,306.